2011
DOI: 10.1007/s10803-011-1305-y
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Dialect Variation by Young Adults with High-Functioning Autism

Abstract: The linguistic profile of people with Autism spectrum disorders typically involves intact perceptual processing, accompanied by deficits in the social functions of language. In a series of three experiments, the impact of this profile on the perception of regional dialect was examined. Young adults with High-Functioning Autism exhibited similar performance to a typically developing comparison group in regional dialect classification and localness rating tasks, suggesting that they can use indexical information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Moreover, precisely because speech accent is a cue to group membership, it is expected that children will perceive the nonnative speaker as less socially desirable than the native speaker. Previous work on the social perception of speech accents has found that listeners rate speakers of lower prestige and nonlocal accents as less desirable on a number of social dimensions (Clopper et al, 2012;Giles, 1970;Luhman, 1990); moreover, this result appears to hold even when the very same person speaks in two different accents (Anisfeld et al, 1962), suggesting it is not properties of the person but associations to the accent that drive the social evaluations. The nonnative speaker in the current experiments had ample experience working with young children and matched the native speaker in general for tone and pacing; moreover, the content of her speech was identical to that of the native speaker because both followed the same script.…”
Section: Speech Accent and Social Learningmentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, precisely because speech accent is a cue to group membership, it is expected that children will perceive the nonnative speaker as less socially desirable than the native speaker. Previous work on the social perception of speech accents has found that listeners rate speakers of lower prestige and nonlocal accents as less desirable on a number of social dimensions (Clopper et al, 2012;Giles, 1970;Luhman, 1990); moreover, this result appears to hold even when the very same person speaks in two different accents (Anisfeld et al, 1962), suggesting it is not properties of the person but associations to the accent that drive the social evaluations. The nonnative speaker in the current experiments had ample experience working with young children and matched the native speaker in general for tone and pacing; moreover, the content of her speech was identical to that of the native speaker because both followed the same script.…”
Section: Speech Accent and Social Learningmentioning
confidence: 86%
“…Adults can reliably categorize individual talkers by their speech accent and can determine whether or not they speak the local regional variety (cf. Clopper & Pisoni, 2004;Clopper, Rohrbeck, & Wagner, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Monophthongization of /ɑj/ is a stereotypical Clopper feature of Southern American English, whereas lowering and fronting of /ɑ/ is a nonstereotyped feature of the Northern Cities vowel shift. Given that the Southern dialect is likely to be familiar through the media and shared social stereotypes (Clopper et al, 2012;Plichta and Preston, 2005), the Southern monophthongal /ɑj/ should be salient to the Midland listeners. By contrast, given that the Northern dialect is nonenregistered (Campbell-Kibler, 2012), the fronted Northern /ɑ/, like the Northern /ɛ, ae/ in experiment 1, is not expected to be salient to Midland listeners.…”
Section: Resultsmentioning
confidence: 99%
“…When they believed the talker was from Michigan, their responses corresponded to standard American English vowels rather than to the local forms, because the target variants are recognized as stereotypically Canadian forms rather than as local forms. The role of social stereotypes in cross-dialect perception is particularly relevant for the Northern dialect of American English (spoken in the northern Midwestern USA) because although this dialect is characterized by the Northern Cities vowel shift (an acoustically distinct system of vowel variants), it is not socially stereotyped as distinct from the more standard Midland dialect, which is spoken in the southern Midwestern USA (Clopper et al, 2012;Niedzielski, 1999). CampbellKibler (2012) has argued that this mismatch between production and perception of the Northern dialect reflects the lack of social enregisterment or social stereotyping of the Northern dialect.…”
Section: Introductionmentioning
confidence: 99%